Response to Psychology as Urban Ministry Presentations - Bentley, Ruth Lewis (Journal of psychology and theology, 1978)
Christian mental health practitioners must recognize the problems in the cities without automatically equating “emotional sickness” to blacks. Such problems are also among poor whites and other minorities. Minority personnel are needed, however, to counteract the feelings of powerlessness and the dependency syndrome blacks experience when relating to whites. Minority workers may need liberation from their own materialistic concerns and actually live in the urban poverty areas, assisting in the task of building “affirmative independent institutions.” Most important for effective urban work, racism must be actively tackled in the worker's own personality and in the structures of society.